Analysis of Urine Podocalyxin in Type 2 Diabetes Mellitus Subjects With and Without Diabetic Nephropathy - Jusni Ekasari Pelu; Liong Boy Kurniawan; Yuyun Widaningsih; Alfian Zainuddin; Husaini Umar; Nurahmi Nurahmi; Theosobia Grace Orno (Universitas Nahdlatul Ulama Surabaya, 2023)
Type 2 diabetes mellitus is the most common cause of diabetes, consist from about 85% of cases. Diabetic nephropathy is a complication of diabetes mellitus in the kidneys which can end up as kidney failure. Podocalyxin (PDX) is a protein expressed in kidney podocytes that is involved in various cancers, and is also essential for kidney development. The research design was carried out using observational and cross-sectional analytic methods with total participants of 25 DM with diabetic nephropathy and 25 DM without diabetic nephropathy with a purposive probability sampling technique. This research conducted at the Endocrine Polyclinic, Clinical Pathology Laboratory, Hasanuddin University Medical Research Center (HUM-RC) Laboratory, Hasanuddin University Hospital, Makassar. The results showed that the urinary PDX level in DM subjects with nephropathy were 1.160 ng/mL and DM without nephropathy were 0.167 ng/mL (p<0.001), the urine albumin/creatinine ratio (ACR) of DM subjects with nephropathy were 644.74 mg/ g and DM without nephropathy of 10.071 mg/g (p<0.001) and the correlation test results of urine PDX and urine ACR in DM subjects with nephropathy (r=0.510; p=0.001). This study concluded that there was a significant difference between urinary PDX in DM with and without diabetic nephropathy, there was a significant difference between urine ACR levels in DM with and without diabetic nephropathy, and there was a relationship between urinary PDX levels and urine ACR in DM subjects with diabetic nephropathy.